A Rare Case of Acquired Transthoracic Littre's Hernia - Curmi, Arthur; Dimech, Anthony P.; Dalli, Rebecca; Mostafa, Ayman; Debono, Joseph (The Surgery Journal, 2019)
Introduction The Littre hernia is a rare complication of Meckel's diverticulum. Meckel's diverticulum is vestigial remnant of the omphalomesenteric duct occurring in approximately 2% of the general population with an estimated 4 to 16% risk of complications. Usual sites of the Littre hernia include inguinal (50%), umbilical (20%), and femoral (20%). We report a case of an acquired transthoracic Littre's hernia occurring through the left part of the diaphragm triggered by a history of traumatic rib fractures associated with alcohol abuse.Case Report A 71-year-old man presented with 4-day history of worsening shortness of breath, colicky lower abdominal pain, and inability to open bowels despite passing flatus, without nausea or vomiting. His past medical history was remarkable for multiple traumatic rib fractures caused by falls which were associated with excessive alcohol consumption. A noncontrast computed tomography (CT) scan of the abdomen and pelvis showed distended jejunal loops containing air/fluid levels likely resulting from herniated jejunum between the left chest wall and left diaphragm. An urgent laparotomy was performed which revealed small bowel and omentum herniating through a small defect in the left posterior hemidiaphragm. The contents of the sac were reduced and a Meckel's diverticulum was found inside the sac, characteristic of Littre's hernia. The diaphragmatic defect was closed and the Meckel diverticulum stapled and excised.Discussion Herniation of Meckel's diverticulum through the diaphragm most commonly occurs in the pediatric population. Acquired transthoracic Littre's hernia is rare and may arise following thoracobdominal trauma caused by surgery, motor vehicle accidents, and falls from height. Left-diaphragmatic tears are characteristically more clinically apparent and symptomatic than the right since the liver often has a protective effect on the right part of the diaphragm. Herniation of abdominal contents in the chest cavity causes respiratory distress and requires urgent surgical correction. Diagnosis is often delayed since diaphragmatic hernia tends to present very late after the initial trauma, subjecting the patient to possible life-threatening complications. While it is easier to reduce the herniated contents and repair the diaphragm via a thoracic approach, laparotomy is often preferred in cases of acute trauma associated with intra-abdominal injuries. Repair of Littre's hernia then consists of resection of the diverticulum and herniorraphy.Conclusion Internal Littre's hernia is usually of congenital origin. This is the first case of a transthoracic Littre's hernia caused by traumatic rib fractures. Hence, it is of utter importance that a clinician is aware of such uncommon pathology.
Keywords: case report; Meckel's diverticulum; Littre's hernia; diaphragmatic defect; transthoracic; acquired